Skin Care in Dermatology: Between Organic Versus Synthetic Products - Riefka Ananda Zulfa; Nelva Karmila Jusuf (Talenta Publisher, 2024)
Background: Various skin care products have been used and played essential roles in maintaining good skin conditions. Over the last few decades, cosmetic industries and pharmacies have evolved and created skin care products according to the needs of each skin type, either based on organic or synthetic products. Objective: This article compares organic and synthetic products based on their ingredients, functions, and side effects. Methods: This is a literature review to analyse the skin care in dermatology. Results: Natural or organic products were produced from natural ingredients, such as plants, flowers, and fruits, while synthetic products were made from a combination of organic chemical compounds. Conclusion: Both products work effectively on the skin according to their contents, but adverse effects can also occur, such as mucocutaneous reactions, edema, and allergies.